A First Introduction to the Finite Element Analysis Program MSC Marc/Mentat - Öchsner, Andreas (Springer International Publishing, 2018)
This book offers a brief introduction to the general-purpose finite element program MSC Marc, focusing on providing simple examples, often single-element problems, which can easily be related to the theory that is discussed in finite element lectures. As such, it is an ideal companion book to classical introductory courses on the finite element method. MSC Marc is a specialized program for non-linear problems (implicit solver), which is distributed by the MSC Software Corporation and commonly used in academia and industry. The documentation of all finite element programs now includes a variety of step-by-step examples of differing complexity, and all software companies offer professional workshops on different topics. Since the first edition of the book, there have been several new releases of Marc/Mentat and numerous changes. This new edition incorporates the latest Marc/Mentat software developments and new examples.